2006
DOI: 10.1074/jbc.m607955200
|View full text |Cite|
|
Sign up to set email alerts
|

On the Processing of Proghrelin to Ghrelin

Abstract: The orexigenic hormone ghrelin is a 28-amino-acid peptide derived from a 99-amino-acid precursor and acylated at Ser-3, which was initially isolated from rat stomach. In addition to stimulating appetite and growth, it also plays various important roles in energy homeostasis and in the cardiovascular and immune systems. Although analysis of its physiological effects has yielded many significant results, much less information is available on its biosynthesis and the mechanism of its acylation. In this report, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
155
0
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(169 citation statements)
references
References 28 publications
(25 reference statements)
7
155
0
7
Order By: Relevance
“…As expected from reports in other species (i.e. Gagnon et al, 2009) and according to the fundamental function of PCSK1 in processing key-gut/intestine prohormones (Zhu et al, 2006), gastric oxyntic mucosa showed a qualitatively higher level of PCSK1gene expression compared with the other tissues ( Figure S1). Therefore, qPCR was used to precisely evaluate the level of expression of this gene in weaning pigs and to evaluate its association with PCSK1 SNPs (see below).…”
Section: Gene Expression Analysessupporting
confidence: 85%
See 2 more Smart Citations
“…As expected from reports in other species (i.e. Gagnon et al, 2009) and according to the fundamental function of PCSK1 in processing key-gut/intestine prohormones (Zhu et al, 2006), gastric oxyntic mucosa showed a qualitatively higher level of PCSK1gene expression compared with the other tissues ( Figure S1). Therefore, qPCR was used to precisely evaluate the level of expression of this gene in weaning pigs and to evaluate its association with PCSK1 SNPs (see below).…”
Section: Gene Expression Analysessupporting
confidence: 85%
“…In particular, this enzyme cleaves proinsulin, proopiomelanocortin, prorenin, proenkephalin, prodynorphin, prosomatostatin and progastrin, generating their corresponding bioactive peptides (Steiner et al, 1996;Muller and Lindberg, 1999;Zhu et al, 2002;Scamuffa et al, 2006). In addition, PCSK1 is required for processing the pre-pro-ghrelin into ghrelin in the gastric mucosa (Zhu et al, 2006). Ghrelin is involved in the control of feed intake and energy metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The post-translational acylation has been shown to occur independently of the proteolytic processing of the ghrelin peptide (10). The hydroxyl group of serine-3 is acylated with an n-octanoic acid or another medium-chain fatty acid, and ghrelin acylation is entirely unique to ghrelin and is required to activate the ghrelin receptor (11), the latter is referred to as active ghrelin.…”
Section: Discussionmentioning
confidence: 99%
“…Another puzzling fact is the lack of evidence for in vivo synthesis of obestatin [13]. Using different prohormone convertases, Zhu et al were not able to observe the formation of obestatin from proghrelin [53]. In addition, plasma obestatin levels measured by radioimmunoassay (RIA) led to varying results which might indicate that the low specificity of these tests could be due to lacking standardization and imprecise values in previous studies [19,36].…”
Section: Discussionmentioning
confidence: 99%